Impact of Pranayama on Neuroplasticity in Psychiatric Disorders: A Narrative Review - Salam, Margaret; K, Archana; Shetty, Sharada; Shetty, Vanitha; T, Vinay Kumar (Indian Journal of Integrative Medicine, 2025)
Background: Psychiatric disorders, such as depression, anxiety, schizophrenia, and PTSD, are associated with impaired neuroplasticity, including structural and functional brain changes. Pharmacological treatments often present adverse effects and limited efficacy in enhancing brain adaptability, highlighting t he need for complementary interventions. Objective: This review explores the potential of pranayama, a yogic breathing technique in promoting neuroplasticity and improving outcomes in psych iatric disorders. Methods: A narrative review was conducted using k eywords "pranayama", "neuroplasticity", and "psychiatric disorders" across databases including PubMed, PubMed Central, and Google Scholar. Inclusion criteria encompassed studies assessing the impact of pranayama on neuroplasticity using neuroimaging, neuro physiological outcomes, and emotional/cognitive functions in psychiatric populations. Results: Pranayama modulates neuroplastic mechanisms via multiple pathways such as enhancing neurotransmitters like GABA, dopamine, serotonin, and glutamate, increasing p refrontal cortex activation and reduces amygdala hyperactivity, improving heart rate variability, indicating enhanced parasympathetic tone and facilitating cortical limbic connectivity, contributing to emotional regulation. Specific practices (e.g., Bhastr ika, Bhramari) were found effective in reducing symptoms of anxiety, depression, and PTSD, and showed potential in improving cognitive and affective functioning in schizophrenia. Conclusion: Pranayama demonstrates promising effects on brain plasticity and mental health through its neurobiological and psychophysiological impact. It presents a safe, non pharmacological approach for managing psychiatric conditions and fostering emotional resilience. However, larger randomized controlled trials and standardized protocols are needed to strengthen clinical recommendations and fully elucidate underlying neural mechanisms.